Pengaruh Kualitas Pelayanan Dan Promosi Terhadap Kepuasan Pelanggan (Survei Pada Pelanggan Gojek Kota Tasikmalaya) - Aditia Saputra (CV. Ulil Albab Corp, 2022)
The objectives of this study was to determine and analyze the quality of service, promotion and customer satisfaction on Gojek in Tasikmalaya City, as well as the effect of service quality and promotion on customer satisfaction on Gojek in Tasikmalaya City. The research method used in this study is a survey method, while the types of data used in this study are primary data and secondary data. The object of this research is Gojek customers in the City of Tasikmalaya, with the sampling technique using the accidental sampling method, where the survey is conducted on Gojek customers in the City of Tasikmalaya. The data analysis technique used is multiple regression analysis. The results of this test prove that the quality of service and promotion have an effect on customer satisfaction at Gojek in Tasikmalaya City.